Image Quality Of T2W TSE Cartesian Versus T2W TSE Blade, A Quantitative Analysis On Axial Cervical MRI - Dwi Rochmayanti; Emi Murniati; Fatimah Fatimah; Akhmad Haris Sulistyadi (Jurnal Imejing Diagnostik (JImeD), 2022)
Backgroud: blurring artifact is an issue in axial cervical MRI using T2 Turbo Spin Echo (TSE) weighted Cartesian. T2W TSE BLADE is potential to substitute its shortcomings. This study aims to analyze the image quality and artifacts between T2W TSE Cartesian and T2W TSE BLADE on axial cervical MRI examination and to determine the better sequence in producing image quality.Methods: this is a quantitative research with descriptive approach. 7 volunteers were scanned for cervical axial examination with T2W TSE, T2W TSE Cartesian and T2W TSE Blade. Images were processed in MathlabTM. SNR of intervertebral disc, spinal cord and CSF were measured using ROI. Image resolution were find out from pixel spacing in DICOM info. Blurring artifact were analyzed by comparing the signal of blurred area to the background noise. Data were analyzed using descriptive statistics.Results: SNR of T2W TSE Cartesian and T2W TSE BLADE were 22,144 and 17,532 (intervertebral disc), 20,952 and 16,786 (spinal cord), and 16,717 and 12,883 (CSF) respectively. Image resolution (mean) were 0,391 pixel/mm (T2W TSE Cartesian) and 0,625 (T2W TSE BLADE). Blurring artifact were 8,161 (T2W TSE Cartesian) and 6,826 (T2W TSE Blade).Conclusion: T2W TSE Cartesian was superior in pixel intensity and SNR, while the blade technique was superior in terms of spatial resolution and artifacts reduction. Thus, it is recommended to be applied in clinical field if the SNR or image detail is the priority.